A Study On The Delay Of The Apartment Housing Project In Central Java Province In The 2021 Budget - Agus Sutiyoso; Antonius; Kartono wibowo (Fakultas Teknik Universitas Pasir Pengaraian, 2023)
The construction phase represents a critical stage in which the construction process unfolds, with the contractor or service provider playing a pivotal role. In the construction project for the acquisition of apartment housing in Central Java Province in the 2021 fiscal year, which had an average implementation period of 120 calendar days and was executed towards the end of the year during a period of high rainfall intensity, significant delays were encountered. This study aims to assess the factors contributing to the delays in the apartment housing procurement project, rank the risks associated with these delays, and propose proactive measures to address and mitigate any potential delays. The significant influencing factors on the role of the Service Provider during the construction phase encompass variables related to planning, scheduling, and cost estimation (X1), resource allocation (X2), administrative bureaucracy (X5), and external contextual conditions (X6). The regression coefficients for these variables are as follows: the variable associated with planning, scheduling, and cost estimation (X1) carries a coefficient of 0.366, the resource allocation variable (X2) bears a coefficient of 0.312, the administrative bureaucracy variable (X5) exhibits a coefficient of 0.538, and the external contextual condition variable (X6) demonstrates a coefficient of 0.204. The variable associated with planning, scheduling, and cost estimation (X1) holds the highest level of significance in influencing the role of the Service Provider during the construction phase, with a regression coefficient of 0.366, indicating its paramount impact. The consequences of delays encompass deferred project milestones, buildings unable to meet their intended function according to the established schedule, subpar work quality, cost overruns, and the project's ultimate completion falling behind the initially planned timeline. To pre-empt and manage these delays effectively, it is imperative for the contractor or service provider to diligently identify and assess project-specific attributes, thoroughly comprehend the scope of work, and promptly seek and implement solutions from the project's inception.